Environmental literacy in higher education: A scopus-based longitudinal bibliometric mapping - Mellyzar Mellyzar; Hernani Hernani; Sirry Alvina; Syarifah Rita Zahara; Fauziana Fauziana; Marhami Marhami (Education and Development Research, 2026)
Environmental literacy (EL) has become a central concern in Education for Sustainable Development (ESD), yet existing reviews remain conceptually fragmented and rarely integrate longitudinal, structural, and thematic evidence in higher education contexts. This study addresses that gap through an analytical–interpretive Scopus-based longitudinal bibliometric mapping that goes beyond descriptive performance reporting toward field-level diagnosis. A dataset of 229 records (2010–2025) was screened using PRISMA 2020 and finalized to 127 eligible English peer-reviewed journal articles, processed through Bibliometric and Biblioshiny in R after author-name normalization, keyword harmonization, and duplicate removal. Findings revealed an accelerating post-2021 growth pattern (R² = 0.628), a Lotka-consistent productivity skew indicating a small recurring core within a long tail of one-time contributors, and a national-anchored collaboration profile in which the United States, Spain, and China dominated while cross-regional partnerships remained limited. Thematic mapping showed conceptual convergence around environmental education, ESD, and sustainability-aligned higher education, while classroom pedagogy and instructional implementation persisted as visible but underdeveloped research fronts reframed here as a pedagogical implementation gap rather than a marginal finding. The study contributes (i) theoretically, by linking bibliometric structure to environmental and sustainability literacy theory and ESD frameworks; (ii) methodologically, by integrating productivity, collaboration, and thematic evolution within a single analytical–interpretive design; and (iii) practically, by offering an evidence base for lecturers, curriculum designers, and institutions seeking to translate sustainability discourse into validated classroom practice.